Time-dependent prognostic value of bispectral index and suppression ratio during targeted temperature management: an early triage tool for treatment escalation plans. (2nd May 2022) - Arbas Redondo, E; Rosillo-Rodriguez, SO; Merino-Argos, C; Marco-Clement, I; Rodriguez-Sotelo, L; Martinez-Marin, LA; Velez-Salas, A; Martin-Polo, L; Caro-Codon, J; Garcia-Arribas, D; Armada-Romero, E; Lopez-De-Sa, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Post-cardiac arrest myocardial dysfunction contributes to morbidity in survivors of cardiac arrest (CA) and, in case of refractory shock, some patients will benefit from aggressive mechanical support. In this scenario, a non-invasive, reliable and real-time estimation of potential neurological recovery is required to establish personalized treatment escalation plans. Methods: We prospectively collected data of bispectral index (BIS) and suppression ratio (SR) monitoring of adult comatose survivors of CA consecutively admitted to an acute cardiac care unit and managed with targeted temperature management (TTM). Neurological status was assessed according to the Cerebral Performance Category (CPC) scale. Results: We included 340 patients, 72.1% had an initial shockable rhythm, 72 (21.2%) were females and their mean age was 61.7 ± 14.3 years. Throughout 3-month follow-up, 210 patients (61.8%) achieved a CPC of 1-2 and 130 (38.2%) a CPC of 3-5. Mean BIS values were significantly higher and median SR lower in patients with CPC 1-2 (Figure 1). An average BIS value >26 during first 12 hours of TTM predicted good outcome with 89.3% sensitivity and 75.2% specificity (AUC of 0.86), while average SR values >24 during first 12 hours of TTM predicted poor outcome (CPC 3-5) with 83.6% of sensitivity and 91.8% of specificity (AUC of 0.92). Hourly BIS and SR values exhibited a good predictive performance (AUC > 0.85), starting as soon as hour 2 for SR and 4 for BIS. Conclusions: BIS and SR real-time monitoring correlates with patient´s potential of neurological recovery after CA. This finding could help establish personalized treatment escalation plans that reduce consequences of inappropriate interventions, economic costs and uncertainty burden of the patient´s family.